Doctrine and Discipline in the Church of Jean Gerson - Caiger, B. J. (The journal of ecclesiastical history, 1990)
The problem of ascertaining by what means and what authority true teachings may be distinguished from false is fundamental to any ecclesiology, since the ecclesiastical community is based, above all, on commonly accepted doctrine. It is a community whose limits are defined — and the parameters within which it operates set — by the body of teachings which is accepted within it as true. Thus, the fundamental practical question which any ecclesiology must address becomes, in effect, who has authority to determine what is taught and what is not; and the answer reveals the main thrust ofthat ecclesiology. In broad terms, two principal, and often conflicting, emphases may be noted: on the community of Christian pilgrims (whom any structure exists to serve), and on the formal ecclesiastical structure (within which the faithful may find security). Pastorally, these emphases are associated to some degree with two different assumptions: either that the believer gains confidence in the institution because of the truth that is taught in it, or that a teaching will be received with confidence by believers ior he reason that it is taught within the institution. In the second case, the pursuit of truth may be subordinated to the support of the expedient.